ANALYSIS OF THE INFLUENCE OF PRODUCT QUALITY, DELIVERY QUALITY, AND SERVICE QUALITY ON CUSTOMER SATISFACTION AT CV UNGGAS KARYA MANDIRI - Jauhari, Muhammad; Timotius Febry Christian; Elia Adryan (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2025)
Customer satisfaction is one of the determining factors of a company’s success. Every company certainly competes to improve customer satisfaction. However, in this case, CV Unggas Karya Mandiri faces several customer satisfaction issues related to products, delivery, and service. Therefore, the purpose of this study is to analyze the influence of product quality, delivery quality, and service quality on customer satisfaction. The research method used in this study is quantitative with SEM-PLS analysis. The research sample was 30 people who are customers of CV Unggas Karya Mandiri. The results of the study indicate that product quality and delivery quality have a significant positive influence on customer satisfaction of CV Unggas Karya Mandiri (a B2B business model trader) so that hypotheses one and two are accepted. However, service quality is not proven to have a significant influence on customer satisfaction, so hypothesis three is rejected. The results of this study can be used as a basis for livestock companies to formulate strategies to increase customer satisfaction by focusing on improving product quality and delivery quality. Keywords: Product Quality, Delivery Quality, Service Quality, Customer Satisfaction, Livestock Industry.